The Influence of Online Learning on Motivation and Learning Outcomes of the Qur'an Hadith in MAN 1 Pasaman - Zakiyatul Hayyu (Ruhama : Islamic Education Journal, 2021)
The purpose of this study is to evaluate and test the influence of online learning on students' learning outcomes in the subjects of the Qur'an Hadith and its motivation in MAN 1 Pasaman. This research is a field study that uses a survey methodology, which can be interpreted as a method to quantitatively describe the basic characteristics of a population. The study participants were grade XII students, with 56 people comprising 25% of the total population of 224 people. After the questionnaire was examined for validity and reliability, the collection of research data was conducted by distributing the questionnaire to respondents. Classic assumption tests, basic linear regression analysis, and partial t-test analysis will be used to evaluate the collected data. The results prove that online learning affects 50.9% of students' learning motivation. Online learning has an influence on learning motivation has a significance value of 0.000 which has implications on the value of significance (0.000) 0.05 which means that online learning affects students' learning motivation.